Disrupted membrane structure and intracellular Ca²⁺ signaling in adult skeletal muscle with acute knockdown of Bin1. - Andoria Tjondrokoesoemo; Ki Ho Park; Christopher Ferrante; Shinji Komazaki; Sebastian Lesniak; Marco Brotto; Jae-Kyun Ko; Jingsong Zhou; Noah Weisleder; Jianjie Ma (PLoS ONE)
Efficient intracellular Ca²⁺ ([Ca²⁺]i) homeostasis in skeletal muscle requires intact triad junctional complexes comprised of t-tubule invaginations of plasma membrane and terminal cisternae of sarcoplasmic reticulum. Bin1 consists of a specialized BAR domain that is associated with t-tubule development in skeletal muscle and involved in tethering the dihydropyridine receptors (DHPR) to the t-tubule. Here, we show that Bin1 is important for Ca²⁺ homeostasis in adult skeletal muscle. Since systemic ablation of Bin1 in mice results in postnatal lethality, in vivo electroporation mediated transfection method was used to deliver RFP-tagged plasmid that produced short -hairpin (sh)RNA targeting Bin1 (shRNA-Bin1) to study the effect of Bin1 knockdown in adult mouse FDB skeletal muscle. Upon confirming the reduction of endogenous Bin1 expression, we showed that shRNA-Bin1 muscle displayed swollen t-tubule structures, indicating that Bin1 is required for the maintenance of intact membrane structure in adult skeletal muscle. Reduced Bin1 expression led to disruption of t-tubule structure that was linked with alterations to intracellular Ca²⁺ release. Voltage-induced Ca²⁺ released in isolated single muscle fibers of shRNA-Bin1 showed that both the mean amplitude of Ca²⁺ current and SR Ca²⁺ transient were reduced when compared to the shRNA-control, indicating compromised coupling between DHPR and ryanodine receptor 1. The mean frequency of osmotic stress induced Ca²⁺ sparks was reduced in shRNA-Bin1, indicating compromised DHPR activation. ShRNA-Bin1 fibers also displayed reduced Ca²⁺ sparks' amplitude that was attributed to decreased total Ca²⁺ stores in the shRNA-Bin1 fibers. Human mutation of Bin1 is associated with centronuclear myopathy and SH3 domain of Bin1 is important for sarcomeric protein organization in skeletal muscle. Our study showing the importance of Bin1 in the maintenance of intact t-tubule structure and ([Ca²⁺]i) homeostasis in adult skeletal muscle could provide mechanistic insight on the potential role of Bin1 in skeletal muscle contractility and pathology of myopathy.